2017
DOI: 10.1111/mec.13975
|View full text |Cite
|
Sign up to set email alerts
|

An allelic series at pax7a is associated with colour polymorphism diversity in Lake Malawi cichlid fish

Abstract: Despite longstanding interest in the evolution and maintenance of discrete phenotypic polymorphisms, the molecular genetic basis of such polymorphism in the wild is largely unknown. Female sex-associated blotched color polymorphisms found in cichlids of Lake Malawi, East Africa represent a highly successful polymorphic phenotype, found and maintained in four genera across the geographic expanse of the lake. Previously, we identified an association with an allelic variant of the paired-box transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…A chimeric, polyallelic origin can explain the cis-regulatory evolution of optix (Wallbank et al 2015) (see also chapter by CD Jiggins in this volume), a transcription factor locus that, like WntA, shows extensive parallelism and multiallelism in the Heliconius genus (Reed et al 2011;Papa et al 2013;Kronforst and Papa 2015;Zhang et al 2016). We expect that further examples of phenotypic radiations will uncover a multiallelic basis, as recently proposed in cichlid fishes (Roberts et al 2016). The fact that we observe genetic heterogeneity shows that multiple variants can swarm in a gene pool and may thus provide the bricks of change to build novel cis-regulatory activities.…”
Section: How When and Why Ligand Genes Are Likely Drivers Of Pattermentioning
confidence: 98%
“…A chimeric, polyallelic origin can explain the cis-regulatory evolution of optix (Wallbank et al 2015) (see also chapter by CD Jiggins in this volume), a transcription factor locus that, like WntA, shows extensive parallelism and multiallelism in the Heliconius genus (Reed et al 2011;Papa et al 2013;Kronforst and Papa 2015;Zhang et al 2016). We expect that further examples of phenotypic radiations will uncover a multiallelic basis, as recently proposed in cichlid fishes (Roberts et al 2016). The fact that we observe genetic heterogeneity shows that multiple variants can swarm in a gene pool and may thus provide the bricks of change to build novel cis-regulatory activities.…”
Section: How When and Why Ligand Genes Are Likely Drivers Of Pattermentioning
confidence: 98%
“…To date, the majority of comparative genetic investigations in cichlids have focused on speciation, trophic morphology, and vision/color patterning (Albertson et al, 2005; Brawand et al, 2014; Gante et al, 2016; Hauser et al, 2017; Hulsey, 2009; Lee et al, 2005; Loh et al, 2008; Owens & Rennison, 2017; Parsons et al, 2014; Roberts et al, 2017; Spady et al, 2005; Streelman et al, 2003). Additional studies have investigated the diverse genetic mechanisms regulating sex determination, and differences in brain organization associated with ecology (Bohne et al, 2013; Sylvester et al, 2013).…”
Section: Cichlids and Lake Malawi Bower Buildersmentioning
confidence: 99%
“…Roberts et al . () studied a widespread female‐associated pigmentation polymorphism—the blotched class of morphs (Fig. A).…”
Section: Cichlid Pigmentation As a Model To Study Polymorphism Develomentioning
confidence: 99%
“…In the present study, Roberts et al . () take a novel approach and combine developmental and population genetics methods to study the emergence and diversification of a colour polymorphism found in four genera, comprising 20 species, of Lake Malawi cichlids (Fig. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation